Dietary electrolyte balance for broiler chickens under moderately high ambient temperatures and relative humidities - Borges, S. A. [UNESP]; Fischer Da Silva, A. V. [UNESP]; Ariki, J. [UNESP]; Hooge, D. M.; Cummings, K. R. (My University, 2003)
Cobb male broiler chicks (1,000) on new litter were used to evaluate effects of dietary electrolyte balance [DEB; Na+K-Cl, milliequivalents (mEq) per kilogram] under tropical summer conditions. Corn-soybean meal-based mash diets had salt (NaCl) alone or in combination with one or more supplements: sodium bicarbonate (NaHCO3), ammonium chloride (NH4Cl), or potassium bicarbonate (KHCO3). A completely randomized design, with five starter and grower feed treatments (control: 145, then 130 mEq/kg; or 0, 120, 240, or 360 mEq/kg throughout) and four replicate pens (1.5 x 3.2 m) per treatment (50 chicks per pen), was used. Diets were analyzed for Na, K, and Cl for confirmation. There were no significant (P < 0.05) effects of treatments on mortality or processing parameters. Water intake increased linearly with increasing DEB, giving higher litter moistures and lower rectal temperatures. Blood HCO3 and pH increased with the highest DEB (360 mEq/kg) causing respiratory alkalosis. The DEB of 240 mEg/kg gave best weight gain and feed conversion ratio, and ideal DEB predicted by regression analyses were 186 and 197 mEq/kg from 0 to 21 d of age and 236 and 207 mEq/kg of feed from 0 to 42 d, respectively. These DEB corresponded to estimated (interpolated) values in predicted optimal 186 to 197 mEq/kg starter of Na 0.38 to 0.40% and Cl 0.405 to 0.39% (K = 0.52%), in 207 to 236 mEq/kg starter, Na 0.409 to 0.445% and Cl 0.326 to 0.372% Cl (K = 0.52%), and in grower Na 0.41 to 0.445%, Cl 0.315 to 0.267% (K = 0.47%).
Keywords: Broiler; Chloride; Dietary electrolyte balance; Heat stress; Sodium; Gallus gallus; Glycine max; Zea mays; bicarbonate; chloride; electrolyte; animal; animal food; blood; body temperature; chicken; diet; drinking; heat; humidity; male; pH; physiology; potassium intake; sodium intake; weight gain; Animal Nutrition Physiology; Animals; Bicarbonates; Body Temperature; Chickens; Chlorides; Diet; Drinking; Electrolytes; Heat; Humidity; Hydrogen-Ion Concentration; Male; Potassium, Dietary; Sodium, Dietary; Weight Gain